Innovative Activity as a Condition for Effective Use of Intellectual Potential - Maydyrova, A.B. (BUKETOV BUSINESS REVIEW, 2019)
The emergence of a global innovation and technological space has determined the modern state economic policy of the Republic of Kazakhstan, aimed at achieving sustainable dynamic development of the country via diversification of economic sectors and waste from the raw materials development trend. In this context, the intensification of innovative activity in enterprises has been mainstreamed that led to the motivation of the formation of the intellectual potential corresponding to the pace and level of innovation. The article provides a descriptive characteristic of the situation in the country concerning the development of innovation activism. Even though the financial crisis has affected almost all of the industrial enterprises, Kazakhstan today has a weak activity in the creation and dissemination of innovations. According to the Statistics Agency of the Republic of Kazakhstan, the share of innovation-active enterprises in the republic was 9.6 % of the total number of respondents. These data lead to the idea that, despite the adoption of state programs that should motivate the innovative activity of the country, unfortunately there are no major changes in this direction.